решить 2 уравнениz:

lg (коень из x-5) + lg ((коень из (2x-3)) +1) = lg30

5^2x - 7^x -35*5^2x +35*7^x=0

1

Ответы и объяснения

Лучший Ответ!
2012-06-07T01:21:33+04:00

1)  lg(sqrt((x-5)*(2x-3)) = lg30 - lg10,  lg(sqrt(2x^2 -13x + 15) = lg3,  sqrt(2x^2 -13x +15)=3, возведем в квадрат:  2x^2 -13x +15 = 9,  2x^2 -13x +6=0,  x=1/2;  6

ОДЗ:  x-5>0 и 2x-3>0,  x>5 и x>1,5. Вывод: x>5

В ОДЗ входит только х=6

2) Группировка и вынесение за скобку.  -34*5^2x +34*7^x=0,  делим на 34

-5^2x + 7^x=0,  5^2x=7^x,  25^x=7^x,  делим на 7^x,    (25/7)^x=1,  x=0